PENGARUH MODAL FISIK, MODAL FINANSIAL, DAN MODAL INTELEKTUAL TERHADAP KINERJA PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BEI TAHUN 2009 S.D 2013) - ', Fitriyati Is '; ', Kamaliah '; ', Gusnardi ' (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This study aims to determine the effect of physical capital, financial capital, intellectual capital have a significant effect on the performance of Food and Beverages companies listed on the Stock Exchange. The research was conducted on Food and Beverages Company Listed on the Stock Exchange in 2009 till 2013, which amounted to 18 companies and is based on the feasibility of the methodology can only be done on a sample of 11 companies. In testing hypotheses make use of statistical analysis using the paired difference test using SPSS analysis tools. The results showed that simultaneous variable physical capital, financial capital, intellectual capital significantly influence a company's financial performance is proxied by ROE. Whereas in partial physical capital and financial capital has no significant influence on the financial performance of the company, only the intellectual capital variables have a significant effect terhadao company's financial performance. From this study it can be concluded that the management of both the physical capital, financial capital and intellectual capital will be able to improve the performance of the company. In addition to physical capital and financial capital Intellectual capital is an important factor that affects the company's ability to remain competitive in the global market so that the manager is expected to know the importance of intellectual capital. And for Bapepam and the Indonesian Institute of Accountants should be able to establish better standards for the measurement and disclosure of intellectual capital.Kata Kunci : Capital, physical, financial, intellectual, ROE